Examining the factors associated with disabilities among hypertensive patients in India - Gopan, Adwaith; BJ, Binu K. (Narra J, 2025)
Hypertension is a major contributor to disability and mortality in India. The aim of this study was to examine the factors associated with activities of daily living (ADL) and instrumental activities of daily living (IADL) disabilities among patients with hypertension in India using secondary data from the longitudinal aging study in India (LASI) wave-1, encompassing a sample of 4,618 respondents. The disablement process model was adopted to categorize the variables into risk, intra-individual, and extra-individual factors. A zero-inflated negative binomial model was employed to identify factors associated with the absence of disabilities and those contributing to their progression. The results indicate that the risk and intra-individual factors had a larger variance in explaining disabilities than the extra-individual factor. Variables such as age, sex, depressive symptoms, psychosomatic symptoms, and physical activity were significantly associated with ADL and IADL disabilities. The findings highlight the need for targeted interventions addressing modifiable risk factors, promoting physical activity, managing depressive symptoms, and enhancing social support to reduce the disability burden in this population and improve the quality of life of hypertensive patients in India.